The main component of an alarm pheromone of kissing bugs plays multiple roles in the cognitive modulation of the escape response - Minoli, Sebastián; Palottini, Florencia; Manrique, Gabriel (Frontiers in Behavioral Neuroscience, 2013)
Innate responses in animals can be modulated by experience. Disturbed adults of the triatomine bug Triatoma infestans release an alarm pheromone (AP) that elicits an escape response in conspecific larvae. The main component of this AP, the isobutyric acid (IsoAc), alone has already shown to generate an escape response in this species. However, not much is known about the modulation of this behavior by non-associative and associative cognitive processes. We present here evidences of the cognitive capacities of T. infestans larvae in an escape context under different conditioning paradigms, including IsoAc in different roles. We show that: 1) the duration of a pre-exposure to IsoAc plays a main role in determining the type of non-associative learning expressed: short time pre-exposures elicit a sensitization while a longer pre-exposure time triggers a switch from repellence to attractiveness; 2) a simple pre-exposure event is enough to modulate the escape response of larvae to the AP and to its main component: IsoAc; 3) IsoAc and the AP are perceived as different chemical entities; 4) an association between IsoAc and an aversive stimulus can be created under a classical conditioning paradigm; 5) an association between IsoAc and a self-action can be generated under an operant conditioning. These results evince that IsoAc can attain multiple and different cognitive roles in the modulation of the escape response of triatomines and show how cognitive processes can modulate a key behavior for surviving, as it is the escaping response in presence of a potential danger in insects.